2020
DOI: 10.17932/iau.tfk.2018.008/2020.301/tfk_v03i1001
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2/COVID-19 Pandemisi

Abstract: ÖzAralık 2019'un son günlerinde Çin'in Hubei eyaleti Wuhan kentinde etiyolojisi bilinmeyen pnömoni vakaları görülmeye başlanmıştır. Kısa süre sonra Dünya Sağlık Örgütü (DSÖ) bu vakalardaki etkenin Coronavirus ailesinin yeni bir üyesi olduğunu duyurmuş ve genetik analizler sonucu bu etkenin 2002 yılında salgın yapan SARS (Şiddetli Akut Solunum Sendromu) ile yüksek oranda benzerlik gösterdiği belirlenmiştir. DSÖ tarafından virüsün güncel isimlendirmesi SARS-CoV-2, oluşturduğu hastalık ise COVID-19 olarak kabul e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
5
0
4
Order By: Relevance
“…In a study with included 520 participants, researchers have found that the rate of using protective materials such as masks and gloves increased by 85-90%. In our study, it was found that 210 people (50%) used masks and 142 people (33.8%) used gloves (8). In our study, it was observed that the answers given to the question of using protective equipment differ according to the gender of the participants, and the rate of using protective equipment in women was higher than that of men.…”
Section: Discussionmentioning
confidence: 46%
“…In a study with included 520 participants, researchers have found that the rate of using protective materials such as masks and gloves increased by 85-90%. In our study, it was found that 210 people (50%) used masks and 142 people (33.8%) used gloves (8). In our study, it was observed that the answers given to the question of using protective equipment differ according to the gender of the participants, and the rate of using protective equipment in women was higher than that of men.…”
Section: Discussionmentioning
confidence: 46%
“…Epidemiologically, COVID‐19 is highly contagious with a survival time of approximately 2 h in the external environment. The incubation period after infection is generally 4–8 days and the longest period of 14 days should be considered as the quarantine period 4 . The most common clinical symptoms of COVID‐19 infection are fever (87.9%), cough (67.7%), fatigue (38.1%), while diarrhea (3.7%) and vomiting (5.0%) are less common 5…”
Section: Introductionmentioning
confidence: 99%
“…The main protection methods were determined as rubbing hands using hand washing or alcohol‐based hand antiseptics, maintaining a safe distance from others to prevent droplet contact, presenting to health institutions/organizations wearing masks, not traveling abroad unless it is compulsory, and complying with the 14‐day quarantine period when returning from abroad. 4 Undoubtedly, healthcare professionals have played the most important role in managing the COVID‐19 pandemic process and solving problems. Nurses, who form the basis of the health system, have struggled at the forefront in this process.…”
Section: Introductionmentioning
confidence: 99%
“…The WHO has issued a series of measures on how people can go about doing that [ 6 ]. Some of these include washing hands (or at least rubbing them with alcohol-based hand sanitizers), standing at a certain distance away from other people, wearing a face mask in public, avoiding travelling abroad unless necessary and complying with a 14-day quarantine period upon returning from abroad [ 7 ]. Strengthening the immune system is also an important means of protection against COVID-19; the weaker our immune systems are, the more susceptible we are to contracting the disease (or any other disease, for that matter) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%